HEPİMİZ İNSANIZ, AMA VİCDANIMIZ DA VAR: VİCDANIN SESİNİ “Bİ SEVMEKTEN… Bİ ÖLÜMDEN…”, “SEVGİLİ NEFRET”, “UNUTULAN” VE “GEÇ KALAN ADAM’IN ÖYKÜSÜ”, HİKÂYELERİNDEN DİNLEMEK - (:unkn) unknown (My University, 2017)
Vicdan evrensel bir duygu olup ilkel insandan modern bireye, tutum ve davranışlara farklı biçim ve boyutlarda yön verir. Vicdani kurallar, nesnel/hukuki yasalardan değil içsel/sessiz yasalar bütününden oluşur. Zaman içinde kişiler masumiyetleri gibi, vicdan duygularını da kaybedebilmektedirler. Kişilerin vicdan duygularını kaybetmelerinde birçok etken olmakla birlikte, en çok hırs ve tamahın rolü vardır. Evrensel/insani bir duygu olan vicdan kavramının edebiyata aksini, daha ilkel anlatılardan izlemek mümkündür. Bu makalede modern Türk edebiyatının önemli yazarlarından Adalet Ağaoğlu'nun "Bi Sevmekten... Bi Ölümden...", Hakan Şenocak'ın "Sevgili Nefret", Sezai Karakoç'un "Geç Kalan Adam'ın Öyküsü", Oğuz Atay'ın "Unutulan" hikâyelerinde vicdan kavramının nasıl işlendiği -yer yer karşılaştırmalar yapılarak- incelenmektedir. Dört hikâyeye de vicdan kavramı etrafında bakıldığında, aslında hikâye kişilerinden hiçbirinin vicdan azabı duyacak bir eylemde bulundukları ya da tavır sergiledikleri söylenemez. Ne Sakine Çiçek ne de Âli Bey'in suç olarak yorumlanabilecek bir eylemi söz konusu değildir. Onların işlemedikleri suçtan dolayı kendi kendilerini suçlu olarak yargılamaları vicdanlarıyla hareket etmeleriyle ilintilidir. "Geç Kalan Adam" ise babasından kendisine tevarüs eden insani duyarlılık ya da vicdani sorumluluk dolayısıyla kendi kendisini yargılayacak; belki de bir başka ihtiyaç sahibine maddi destek olunca vicdanı rahatlayacaktır. "Unutulan" hikâyesinde eylemin (eylemsizliğin demek daha doğru olacaktır) suç, modern öznenin de suçlu olup olmadığı son derece göreceli bir durumdur. Modern hayatın keşmekeşi içinde yorulduğu/boğulduğu için ne anılarını ne de değerlerini hatırlayabilir

Conscience, an universal emotion, takes turn from attitudes or behaviours of individual from troglodyte to modern man. Conscientious rules derives from not objective/legal laws but body of internal/silent laws. Over time, individuals misplaces not only innocency but also conscientious emotions. Generally, it is played part in greed and cupidity beside other factors. From primitive narrations to modern narrations, it is possible to observe fictional reflections of conscience as an universal/humanistic emotion. In this work, it will be examined how to be processed conscience in the stories named "Bi Sevmekten... Bi Ölümden…" (by Adalet Ağaoğlu), "Sevgili Nefret" (by Hakan Şenocak), "Geç Kalan Adam'ın Öyküsü" (by Sezai Karakoç), "Unutulan" (by Oğuz Atay) by comparison from place to place. When we look at the four stories around the notion of conscience, it can not be said that none of the people in the story are in an action to hear conscientious objection or exhibit an attitude. Neither the Sakine Çiçek nor Âli Bey’s acts can be interpreted as a crime.What they do not do is judge themselves guilty for the crime, because they are related to their actions with the conscience. "Geç Kalan Adam’ın Öyküsü" will judge himself for his human sensitivity or conscientiousness, which inherits him from his father; perhaps his conscience will be relieved by financial support for another need. In the "Unutulan" story, the act (the inaction will be more accurate) is a very relative situation, whether or not the modern subject is guilty. He can remember neither the memories nor the values because he is tired/tired of the rush of modern life. When we look at the four stories ("Bi Sevmekten... Bi Ölümden...", "Sevgili Nefret", "Unutulan", "Geç Kalan Adam’ın Öyküsü") around the notion of conscience, it can not be said that none of the people in the story are in an action to hear conscientious objection or exhibit an attitude. Sakine Çiçek and Âli Bey constantly judge their own self, conscience rage. In fact, neither the Sakine Çiçek nor the Âli Bey is an act that can be interpreted as a crime. What they do not do is to blame themselves for guilty, because they are guilty of having to act with supermasters / super-masters. "Geç Kalan Adam" will judge himself for his human sensitivity or conscientious responsibility, which he inherited from his father; perhaps his conscience will be relieved by financial support for another need. In the "Unutulan" story, the act (which would be more accurate if it means being inaction) is a very relative situation, whether modern subject is guilty or not. Especially in the modern era where the collectives they live in are alien to themselves and all traditional values, it can not be mentioned that neither the dead parent nor the exwife can be described as a crime either in the eyes of the law or society. However, it is often the case that the voices of one's conscience will dominate the judiciary, the legal judgments of society, or the point of view. Silent laws in the psyche world of the quiche, Âli Bey, Sakine Çiçek and "Geç Kalan Adam’ın Öyküsü" constantly judge the modern essay in the “Unutulan”/"Forgotten" story from time to time. Sakine Çiçek and Âli Bey constantly blame themselves, while the modern woman in the "Unutulan" story always tries to justify herself. However, it can not be said that the woman in the "Unutulan" story is too selfish. While Sakine Çiçek and Âli Bey are examples of traditional human beings, the woman in the "Unutulan" story is a modern single individual. Modern life can remember neither memories nor their values because they are tired / drowned in the rush of life
WE ARE HUMAN, BUT WE HAVE ALSO AN CONSCIENCE: TO LISTEN VOICE OF CONSCIENCE FROM THE STORIES NAMED "Bİ SEVMEKTEN... Bİ ÖLÜMDEN...", "SEVGİLİ NEFRET", "GEÇ KALAN ADAM'IN ÖYKÜSÜ", "UNUTULAN"